1998
DOI: 10.1177/104990919801500205
|View full text |Cite
|
Sign up to set email alerts
|

Comfort and incidence of abnormal serum sodium, Bun, creatinine and osmolality in dehydration of terminal illness

Abstract: This prospective clinical study was undertaken to evaluate the effect of spontaneous food/fluid intake on serum sodium and comfort levels in a population of terminal patients (n = 31) receiving clysis or intravenous hydration. The median and mode of serum sodium were within normal limits and 56 percent of the patients were eunatremic. There was no statistically significant difference in comfort scores between predehydration and dehydration phases, and 85 percent had an optimal comfort score. A statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…This polarization probably has its origins in the historic schism between the relatively aggressive approach of the hospital or biomedical model of management and the more conservative approach of traditional hospice care [33]. From the traditional hospice perspective, provision of intravenous or subcutaneous fluids to patients with advanced disease largely entails an unnecessary intervention and consequent burden for the patient [3,32,67,106].…”
mentioning
confidence: 99%
“…This polarization probably has its origins in the historic schism between the relatively aggressive approach of the hospital or biomedical model of management and the more conservative approach of traditional hospice care [33]. From the traditional hospice perspective, provision of intravenous or subcutaneous fluids to patients with advanced disease largely entails an unnecessary intervention and consequent burden for the patient [3,32,67,106].…”
mentioning
confidence: 99%
“…Dehydration, as indicated by an increased BUN/Cr ratio or USG (Aronson et al., 2008; Vullo‐Navich et al., 1998; Weinberg et al., 1994), is known to be relatively common among patients who have experienced stroke (Rowat, Graham, & Dennis, 2012). Some studies have reported the possible relationship of dehydration with poor neurological function outcome of acute ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the possible relationship of dehydration with poor neurological function outcome of acute ischemic stroke patients. For example, BUN/Cr ratio as a marker of dehydration status was an independent predictor of early neurological deterioration among patients who had suffered acute ischemic stroke (Aronson et al., 2008; Lin et al., 2011; Vullo‐Navich et al., 1998; Weinberg et al., 1994). A correlation between BUN/Cr ratio ≥15 and worse outcome was also found in stroke patients (Schrock et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations